Clinical risk scores for the prediction of incident atrial fibrillation: a modernized review - Louka Anna Maria (Sciendo, 2021)
Atrial fibrillation (AF) is considered the most common sustained arrhythmia. Major cardiovascular risk factors that have been identified to initiate and perpetuate AF include age, sex, arterial hypertension, heart failure, valvular heart disease and diabetes mellitus. In the literature, several studies aimed to formulate easily – applied and accurate risk stratification scores, based on antecedent cardiovascular events, comorbidities and biomarkers for the prediction of new-onset AF. The present narrative review addresses the most universally accepted and efficient clinical scores, with an extended applicability in different populations and ages, particularly scores derived from the Framingham Heart Study, the Atherosclerosis Risk in Communities, the Malmo Diet and Cancer Study, as well as the CHARGE-AF, the CHADS2, CHA2DS2-VASc, HATCH and CH2EST scores. Identification of incident AF can be challenging, thus dictating for utilization of validated clinical instruments in everyday clinical practice.